Quantifying consistency of technique in swimming - Rowlands, D. D.; Wada, T.; Lee, J.; James, D. A. (Journal of Fitness Research, 2016)
Swimming consists of a repetitive action which can be visualised using overlay and phase portrait techniques to determine the consistency of the swimming action. However, this does not lead to a quantifiable value for the consistency. This paper uses curve fitting techniques on the body roll data measured by inertial sensor gyroscopes to quantify the consistency of action of two swimmers. It was found visually that the consistency between the two swimmers were different and the curve fitting technique also showed a difference indicating that the technique can be useful in quantifying the consistency of the action.